Evaluating the Impact of Computerized Accounting Information System on the Economic Performance of Construction Companies in Iraq - Hussain Al-Hashimy, Hisham Noori; Said, Ilias; Yusof, Nor’Aini; Ismail, Radzi (Informatica, 2022)
The aim of this study is to determine the effect of the three contexts of Computerized Accounting Information System (technological, organizational, and environmental) on construction companies’ economic performance. To achieve this aim, a survey was conducted on 208 construction companies that adopted CAIS with 152 valid responses received, representing a 73% rate of useable responses. The data analysis was carried out adopting the partial least squares structural equation modeling (PLS-SEM) technique. The results indicate that the technological and organizational context of CAIS had a positive significant effect on construction companies’ economic performance while the environmental context had a negative significant effect on construction companies’ economic performance. This research’s findings are significant to the practice of adopting CAIS technology on construction projects in developing countries since it provides the likely effect of the various contexts of CAIS on the economic performance of construction companies which will be beneficial for planning and decision-making to the construction companies’ management. Theoretically, the findings of this study will enrich existing literature by providing empirical proof of the variable effect of the various CAIS contexts on construction companies’ economic performance in Iraq which has not been considered in the existing literature. This study is limited to construction companies in Iraq.